Völlig Losgelöst!? Bodies, Space and Digital Games (KULT_online, 2014)
Digital games involve more than building up heroes and shooting down monsters. And gamers do not simply sit passively in front of a screen for hours or days on end. Build ‘em Up – Shoot ‘em Down explores the role of the human body, both within and in front of digital games. This anthology includes eighteen essays in both English and German that cover topics such as identity, interfaces, gender, and death in games. The essays offer various methodologies of exploration, analyses of multiple game genres and different contexts of use from numerous disciplinary fields and perspectives. They produce not only a number of insights into questions of corporeality in games, but also uncover further questions for future research. Finally, they reveal the profuse and complex ways digital games induce the human body to states of play.